2012
DOI: 10.1002/sys.21206
|View full text |Cite
|
Sign up to set email alerts
|

A System‐Aware Cyber Security architecture

Abstract: As exemplified in the 2010 Stuxnet attack on an Iranian nuclear facility, attackers have the capabilities to embed infections in equipment that is employed in nuclear power systems. In this paper, a new systems engineering focused approach for mitigating such risks is described. This approach involves the development of a security architectural formulation that integrates a set of reusable security services as an architectural solution that is an embedded component of the system to be protected. The System‐Awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“…Leonard also focused on DoD cyber systems and found that the DoD needs to move beyond developing survivable cyber systems to incorporate resiliency in their cyber systems. Jones and Horowitz discuss the development of system‐aware cyber security architectures in their work that emphasizes designing cyber systems that can detect threats to ensure performance. They expand on this work by developing a scoring scheme for evaluating cyber‐secure architectures during development .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Leonard also focused on DoD cyber systems and found that the DoD needs to move beyond developing survivable cyber systems to incorporate resiliency in their cyber systems. Jones and Horowitz discuss the development of system‐aware cyber security architectures in their work that emphasizes designing cyber systems that can detect threats to ensure performance. They expand on this work by developing a scoring scheme for evaluating cyber‐secure architectures during development .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The CPs include enough specificity to aide integrators in the application of advanced systems engineering strategies for addressing cyber security concerns. As one example, vendor diversity is a key aspect of cyber resilience [Jones and Horowitz, ], and the CP addresses this requirement. The CPs form a foundation for the reference architecture proposed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To combat the threat posed by cyber attacks on cyber physical systems, a UValed research team proposed a system-aware, sentinel-based cyber security concept, complementing existing network and perimeter security solutions by adding an additional layer of defense (Jones et al 2013;Jones and Horowitz 2012;Horowitz and Pierce 2013). The term "system-aware" indicates that the design of sentinels must directly account for how engineers design the system being protected and its operation, in contrast to network and perimeter security solutions.…”
Section: System-aware Cyber Securitymentioning
confidence: 99%